Pattern of bone erosion and bone proliferation in psoriatic arthritis hands: a high-resolution computed tomography and radiography follow-up study during adalimumab therapy. (May 2014) - Poggenborg, RP; Bird, P; Boonen, A; Wiell, C; Pedersen, SJ; Sørensen, IJ; Madsen, OR; Slot, O; Møller, JM; Bøyesen, P; Hasselquist, M; Østergaard, M
Abstract : Objectives: To investigate the pattern and development of bone erosion and proliferation in patients with psoriatic arthritis (PsA) during treatment with adalimumab, using high-resolution computed tomography (CT) and conventional radiography. Method: Forty-one biologic-naïve PsA patients were initiated with adalimumab 40 mg subcutaneously every other week. CT and radiography of the 2nd–5th metacarpophalangeal (MCP), proximal interphalangeal (PIP), and distal interphalangeal (DIP) joints were conducted at baseline (n = 41) and after 24 weeks (n = 32). Changes in bone erosion and proliferation are described and the imaging modalities compared. Results: Ninety percent of bone erosions detected by CT were located in the metacarpal heads, and most frequently in the 2nd-3rd MCP joints. Radial (37%) and ulnar (31%) surfaces were more frequently eroded than dorsal (10%) and palmar (22%) sites. Using CT, bone proliferations were located primarily on the sides of the distal part of the DIP joints (43% of all proliferations), but also proximally in DIP (17%) and MCP joints (27%). For bone erosions and proliferations, respectively, radiography showed a low sensitivity (17% and 26%), but a high specificity (98% and 95%) and accuracy (93% and 87%), with CT as the gold standard reference. Neither CT nor radiography revealed statistically significant changes in bone erosion or proliferation scores between baseline and follow-up. Conclusions: Patterns of bone erosion and proliferation in PsA hands were revealed in more detail by CT than by radiography. No overall progression or repair could be detected during adalimumab treatment with either of the methods.